(untitled) (Fiep Bulletin - online, 2025)
Introduction: During adolescence, habits are created for adult life, so the high level of sedentary behavior and the low level of physical activity are worrying elements at this stage of life. Objective: This study sought to identify sedentary behaviors among school adolescents and which factors are associated. Methods: This is a narrative review of the literature of a descriptive nature, as it will address the levels of sedentary behavior and associated factors among adolescents, through articles in indexed databases. Results: The main findings of this review revealed that rates of sedentary behavior and physical inactivity are high among adolescents, noting numerous factors that are associated, such as age, sex, place of residence, school, sociodemographic characteristics, parental supervision, time in front of screens and their lifestyle in recent years. Conclusion: According to the literature analyzed, the factors that can lead to sedentary behavior are clear. They state that it is possible to implement effective interventions to reduce a sedentary lifestyle, with the inclusion of healthy habits in their routine, such as physical activity as a routine, however, the attention of parents and/or guardians must be constant at this stage of life, as well as family intervention are fundamental factors for the adoption of new habits.